Physical Modeling of Exsplosion - Abdullayeva, N.Z.; Ahmadov, Sh.A.; Yaryeva, A.M. (Herald of Azerbaijan Engineering Academy, 2024)
In the article, the physical modeling of the explosion, the excess pressure and the factors affecting the shock wave generated during the explosion were analyzed. The physical modeling of the explosion in different prisms has been considered, and so far only the atomic and electronic point of view has been examined, and the effect of the processes taking place in the atom on the excess pressure and the shock wave has been investigated.